Intraoperative peritoneal lavage cytology offers prognostic significance for gastric cancer patients with curative resection. Issue 5 (22nd May 2017) - Higaki, Eiji; Yanagi, Shinya; Gotohda, Naoto; Kinoshita, Takahiro; Kuwata, Takeshi; Nagino, Masato; Ochiai, Atsushi; Fujii, Satoshi
Abstract : Outcomes of patients with gastric cancer who exhibit positive peritoneal lavage cytology findings (CY + ) vary by diagnostic methods because of quantitative and qualitative cancer cell diversity. This study sought to establish practical diagnostic criteria for performing curative resections, based on peritoneal lavage cytology findings in gastric cancer patients. We enrolled 1028 patients with gastric cancer who underwent R0/1 ( n =  911) or R2 ( n =  117) resections and analyzed relationships between cancer cell findings in peritoneal lavage fluid and clinicopathological factors in the R0/1 group. We found 68 patients with CY + status. Receiver operating characteristic analyses and multivariate analyses showed that the presence of ≥1 signet ring cell, ≥5 cell clusters or ≥50 isolated cancer cells in peritoneal lavage fluid predicted poor prognoses in the 68 CY + patients. High‐risk CY + group patients with at least one of the above predictors had the highest hazard ratio (HR = 3.28, P  <   0.001). The remaining (low‐risk) patients had a survival curve similar to that of patients with a normal cytology. The high‐risk CY + patients who underwent R1 resection had poor prognoses despite no macroscopic peritoneal metastasis (2% 5‐year survival)—equivalent to that of patients who underwent R2 resection. The CY + criteria defined in this study could help identify candidates for curative resection as an initial therapy for gastric cancer. Abstract : Peritoneal lavage cytology findings that include ≥1 signet ring cells, ≥5 cell clusters, or ≥50 isolated cancer cells were associated with worse prognosis in gastric cancer, and could indicate patients who would benefit from gastrectomies.